Intervensi Spiritual Terhadap Tingkat Kecemasan Pasien Kanker Serviks - Andi Ijriani; Rahmawati Rahmawati (Jurnal Ilmiah Kesehatan (JIKA), 2021)
This study aimed to analyze the influence of spiritual intervention on the level of client anxiety of cervical cancer in the department. Dr. Wahidin Sudirohusodo Makassar. This type of research is a quasi-experimental approach to the design used was a pretest-posttest control group design. Interventions that give the spiritual intervention with a sample of 40 of 20 people and a control group of 20 people groups. The results showed that there are different levels of patient anxiety before and after spiritual intervention, that of the treatment group pre test and post test 2,10 treatment group to 1,75 with the level of decline was 0,35 (35%). 0,000 with significant value less than 0.05 means that there are differences in anxiety patients on pre-test and post-test groups. This change occurred because of the influence of spiritual interventions provided to patients with cervical cancer thus reducing patient anxiety scores. Suggested at the hospital, doctors, nurses, medical teams, other paramedics need to pay attention to the spiritual aspects of patients as an adjunct therapy in the treatment of physical illnesses and mental particularly terminally ill.